Surface Characteristics and Cell Adhesion Behaviors of the Anodized Biomedical Stainless Steel - Heng-Jui Hsu; Chia-Yu Wu; Bai-Hung Huang; Chi-Hsun Tsai; Takashi Saito; Keng-Liang Ou; Yen-Chun Chuo; Kuan-Ling Lin; Pei-Wen Peng (Applied Sciences, 2020)
In this study, an electrochemical anodizing method was applied as surface modification of the 316L biomedical stainless steel (BSS). The surface properties, microstructural characteristics, and biocompatibility responses of the anodized 316L BSS specimens were elucidated through scanning electron microscopy, X-ray photoelectron spectroscopy, X-ray diffractometry, transmission electron microscopy, and in vitro cell culture assay. Analytical results revealed that the oxide layer of dichromium trioxide (Cr2O3) was formed on the modified 316L BSS specimens after the different anodization modifications. Moreover, a dual porous (micro/nanoporous) topography can also be discovered on the surface of the modified 316L BSS specimens. The microstructure of the anodized oxide layer was composed of amorphous austenite phase and nano-Cr2O3. Furthermore, in vitro cell culture assay also demonstrated that the osteoblast-like cells (MG-63) on the anodized 316L BSS specimens were completely adhered and covered as compared with the unmodified 316L BSS specimen. As a result, the anodized 316L BSS with a dual porous (micro/nanoporous) oxide layer has great potential to induce cell adhesion and promote bone formation.